2021
DOI: 10.1109/tnsre.2021.3123696
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the General Anesthesia Induced Loss of Consciousness by Cross Fuzzy Entropy-Based Brain Network

Abstract: Although the spatiotemporal complexity and network connectivity are clarified to be disrupted during the general anesthesia (GA) induced unconsciousness, it remains to be difficult to exactly monitor the fluctuation of consciousness clinically. In this study, to track the loss of consciousness (LOC) induced by GA, we first developed the multi-channel cross fuzzy entropy method to construct the time-varying networks, whose temporal fluctuations were then explored and quantitatively evaluated. Thereafter, an alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…However, the effects of anesthesia on DMN architecture within the state itself is unclear. The time-series uctuations in FC potentially modulate the brain network 38,39 and re ects the effects of anesthesia 40 . Thus, we calculated the top 20% of connections based on fuzzy entropy to measure exibility in the time-series uctuations in FC across the different states (Fig.…”
Section: Paradoxical Variations In Dmn Architecture Are Frequency Dep...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of anesthesia on DMN architecture within the state itself is unclear. The time-series uctuations in FC potentially modulate the brain network 38,39 and re ects the effects of anesthesia 40 . Thus, we calculated the top 20% of connections based on fuzzy entropy to measure exibility in the time-series uctuations in FC across the different states (Fig.…”
Section: Paradoxical Variations In Dmn Architecture Are Frequency Dep...mentioning
confidence: 99%
“…Thereafter, the top 20% of network edges with the largest fuzzy entropy were used to identify the exible network architectures of the DMN. Information regarding fuzzy entropy has been described in the literature 40,72 .…”
Section: Functional Network Analysis and Temporal Uctuations In The N...mentioning
confidence: 99%
“…Many studies have confirmed that complexity and brain networks are effective indicators for evaluating the level of consciousness during GA in normal subjects [17][18][19]. Complexity indices and network indices are related but represent different aspects of a system.…”
Section: Introductionmentioning
confidence: 99%
“…Using intracortical recordings in macaque monkeys, Schroeder et al [12] showed that ketamine anesthesia inhibits communication among structurally linked cortical regions. By investigating functional connectivity and constructing time-varying networks, Li et al [13], [14] monitored the fluctuation of consciousness during anesthesia. Using network nodes (brain regions) and the FC between nodes, FNA provides a standard method to quantify and study functional integration and segregation of the brain.…”
Section: Introductionmentioning
confidence: 99%